Long‐read‐based draft genome sequence of Indian black gram IPU‐94‐1 'Uttara': Insights into disease resistance and seed storage protein genes. Issue 3 (28th June 2022) - Ambreen, Heena; Oraon, Praveen Kumar; Wahlang, Daniel Regie; Satyawada, Rama Rao; Katiyar‐Agarwal, Surekha; Agarwal, Manu; Jagannath, Arun; Kumar, Amar; Budhwar, Roli; Shukla, Rohit Nandan; Goel, Shailendra
Abstract: Black gram [ Vigna mungo (L.) Hepper var. mungo ] is a warm‐season legume highly prized for its protein content along with significant folate and iron proportions. To expedite the genetic enhancement of black gram, a high‐quality draft genome from the center of origin of the crop is indispensable. Here, we established a draft genome sequence of an Indian black gram cultivar, 'Uttara' (IPU 94‐1), known for its high resistance to mungbean yellow mosaic virus. Pacific Biosciences of California, Inc. (PacBio) single‐molecule real‐time (SMRT) and Illumina sequencing assembled a draft reference‐guided assembly with a cumulative size of ∼454.4 Mb, of which, 444.4 Mb was anchored on 11 pseudomolecules corresponding to 11 chromosomes. Uttara assembly denotes features of a high‐quality draft genome illustrated through high N50 value (42.88 Mb), gene completeness (benchmarking universal single‐copy ortholog [BUSCO] score 94.17%) and low levels of ambiguous nucleotides (N) percent (0.0005%). Gene discovery using transcript evidence predicted 28, 881 protein‐coding genes, from which, ∼95% were functionally annotated. A global survey of genes associated with disease resistance revealed 119 nucleotide binding site–leucine rich repeat (NBS‐LRR) proteins, while 23 genes encoding seed storage proteins (SSPs) were discovered in black gram. A large set of microsatellite loci were discovered for marker development in the crop. Our draft genome of an Indian black gram provides the foundational genomic resources for the improvement of important agronomic traits and ultimately will help in accelerating black gram breeding programs. Core Ideas: A ∼454.4‐Mb draft genome of an Indian black gram was assembled based on SMRT and Illumina sequencing. Around 444.4 Mb (∼97.8%) of the assembly was anchored onto 11 pseudomolecules based on the reference‐guided method. Large collinear blocks representing high synteny among Vigna species were detected. Gene discovery predicted 28, 881 gene models, of which, 95% were functionally annotated. Disease resistance genes and SSPs were investigated for deployment in crop improvement.